2016
DOI: 10.1016/j.neuroimage.2015.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Conflict monitoring in speech processing: An fMRI study of error detection in speech production and perception

Abstract: 26To minimize the number of errors in speech, and thereby facilitate 27 communication, speech is monitored before articulation. It is, however, unclear at 28 which level during speech production monitoring takes place, and what mechanisms 29 are used to detect and correct errors. The present study investigated whether 30 internal verbal monitoring takes place through the speech perception system, as 31proposed by perception--based theories of speech monitoring, or whether 32 mechanisms independent of perceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
67
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 85 publications
(7 reference statements)
9
67
2
Order By: Relevance
“…Thus, we conclude that language specific control mechanisms remain relatively intact and unchanged in aging bilinguals, and that the main effect of aging (especially the increased rate of intrusion errors which can not simply be attributed to age-related slowing), should be attributed to decline in executive control ability, and a role this plays in monitoring upcoming speech after it is planned (Gauvin, De Baene, Brass, & Hartsuiker, 2016; Nozari, Dell, & Schwartz, 2011; Postma, 2000). On this view, relatively automatic aspects of language control remain intact in aging (e.g., grammatical encoding and the propensity to allow language switches in some, perhaps cross-linguistically more syntactically congruous contexts, and for some parts of speech, more than others).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Thus, we conclude that language specific control mechanisms remain relatively intact and unchanged in aging bilinguals, and that the main effect of aging (especially the increased rate of intrusion errors which can not simply be attributed to age-related slowing), should be attributed to decline in executive control ability, and a role this plays in monitoring upcoming speech after it is planned (Gauvin, De Baene, Brass, & Hartsuiker, 2016; Nozari, Dell, & Schwartz, 2011; Postma, 2000). On this view, relatively automatic aspects of language control remain intact in aging (e.g., grammatical encoding and the propensity to allow language switches in some, perhaps cross-linguistically more syntactically congruous contexts, and for some parts of speech, more than others).…”
Section: Discussionmentioning
confidence: 83%
“…One notable exception in this regard was older bilinguals’ lower rate of self-corrections of intrusion errors (i.e., rate of partial relative to full intrusion errors; see Figure 6). This result led us to suggest that executive control ability may play an important role in monitoring upcoming speech after it is planned (see Discussion section in Experiment 2; Gauvin et al, 2016; Nozari et al, 2011). Also of particular interest here was the absence of an interaction between aging and language dominance on within-language errors; both aging effects and dominance effects were highly robust in Experiment 2, but we obtained no evidence that older bilinguals had particular difficulty controlling speech in a less proficient language.…”
Section: Discussionmentioning
confidence: 95%
“…In this case, severe verbal apraxia and lesions in the ventral motor and premotor areas would be expected to result in less sIS, not more, as we found in our analyses. Another recent functional imaging study on unimpaired participants found monitoring of both inner and aloud speech was associated with increased activation in a domain-general error detection area, the ACC, as well as the posterior IFG (Gauvin, De Baene, Brass, & Hartsuiker, 2015). These results suggest that lesions in the posterior IFG might cause unreliable self-monitoring, not a relationship with frequency of sIS as we found.…”
Section: Discussionmentioning
confidence: 99%
“…For speech perception, functional neuroimaging studies have reported activity in response to syllables 50, 51, words 52, 53, and sentences 54, 55, 56, 57, 58, 59. Such responses seem to be modulated by the difficulty of speech processing and comprehension.…”
Section: Auditory Information In Sma and Pre-smamentioning
confidence: 99%